Sniffer Pro Network Optimization and Troubleshooting Handbook - Shimonski, Robert J. (Syngress Publishing, 2011)
The only book dedicated Sniffer, a powerful tool created for real-time enterprise network fault diagnosis and performance management. Sniffer Network Optimization and Troubleshooting Handbook introduces the reader to the vast functionality of the suite of Sniffer Solutions from Network Associates but ultimately focuses on the affordable and most widely used Sniffer Product - Sniffer Pro LAN Network Analyzer. This book will begin with the basic features of Sniffer Pro LAN and then move the reader through the impressive tips and tools available for gathering data, analyzing, troubleshooting, resolving and securing problems on their network. In today's day and age a company is judged by the quality of it is network. To ensure sustained network performance and to avoid costly network downtime, network administrators need to be proficient with advanced networking monitoring and troubleshooting solutions, like Sniffer, to be able to detect, observe, and resolve network problems before these problems impact users or customers. Sniffer from Network Associates is a suite of tools including Sniffer Portable Analysis Suite, Sniffer Distributed Analysis Suite, Sniffer Reporting, Sniffer Optical, and Sniffer Wireless. With a clear market leadership, Sniffer Solutions are employed in over 80% of the enterprise networks of the Fortune 100. Sniffer has also received wide industry acclaim from the experts and its everyday users. In 2000 Sniffer was named one of the 10 most computer products of the decade by Network Computing Magazine. It also received the "Editor's Choice" award from PC Magazine during the second quarter of 2001.